Reversible Repression of Early Enzyme Synthesis in Bacteriophage T4-infected Escherichia coli - Cohen, Paul S. (1968)
A mutant of Escherichia coli B, defective in its accumulation of K(+), was found to synthesize protein at a rate proportional to the level of this cation in the growth medium. When bacteriophage T4-infected cells were incubated in growth medium containing 1 mm K(+), phage deoxyribonucleic acid (DNA) was synthesized at a rate 25% that of normal, and phage protein was synthesized at a rate of 50% of normal. Deoxycytidine pyrophosphatase, a phage-directed early enzyme, shut off at a level of 55% that of normal when infected cells were incubated in medium containing 1 mm K(+). However, deoxycytidine pyrophosphatase synthesis resumed in these cells when they were shifted to medium containing the normal K(+) concentration (33 mm). DNA synthesis also attained the rate characteristic of this K(+) concentration. These results suggest that phage DNA synthesis is not sufficient to repress early protein formation and also indicate that the inhibitor of early protein formation is an early function whose synthesis is sensitive to the same repression as that of the early proteins.